Improved diagnostics targeting c-MET in non-small cell lung cancer: expression, amplification and activation? - Watermann, Iris; Schmitt, B.; Stellmacher, F.; Müller, J.; Gaber, R.; Kugler, Ch.; Reinmuth, N.; Huber, R. M.; Thomas, Michael; Zabel, P.; Rabe, K. F.; Jonigk, D.; et al. (Diagnostic pathology, 2018)
Several c-MET targeting inhibitory molecules have already shown promising results in the treatment of patients with Non-small Cell Lung Cancer (NSCLC). Combination of EGFR- and c-MET-specific molecules may overcome EGFR tyrosine kinase inhibitor (TKI) resistance. The aim of this study was to allow for the identification of patients who might benefit from TKI treatments targeting MET and to narrow in on the diagnostic assessment of MET.
Gesehen am 29.06.2020